Ethnocultural Processes during the Uzbek Khanates (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article aims to correctly illuminate aspects of the history of the Motherland that are still unknown to us, especially the traditional inter-ethnic processes in the territory of the Uzbek khanates, as well as the ethnic formation, composition and main stages of the Uzbek people and population, as well as historical realities, based on its completion, clarification and objective assessment.